Do extra compulsory physical education lessons mean more physically active children - findings from the Childhood Health, Activity, and Motor Performance School study Denmark (The CHAMPS-study DK) - Møller, N. C.; Tarp, J.; Friis Kamelarczyk, E.; Brønd, J. C.; Klakk, H.; Wedderkopp, N. (International Journal of Behavioral Nutrition and Physical Activity, 2014)
Background: Primarily, this study aims to examine whether children attending sports schools are more active than their counterpart attending normal schools. Secondary, the study aims to examine if physical activity (PA) levels in specific domains differ across school types. Finally, potential modifications by status of overweight/obesity and poor cardio-respiratory fitness are examined.